Influence on the sporting result of the concentration of attention process and time taken in the case of weight lifters. - Baroga, L. (1973)
Characteristics of the imagery and attentional activities of weight lifters (N = 446) from 37 different countries at national and international competitions (1966-1972) were reported. Data were obtained by interviews and supplemented with information from doctors and trainers. 1. Mediocre weight lifters displayed a short period of mental preparation with non-activity thought content (e.g., friends, family, failures, nothing). 2. The best lifters mentally rehearsed a positive performance of the exact skill. 3. Each exact-skill representation had appropriate motor counterparts as evidenced by EEG patterns. 4. The length of time spent in rehearsal was constant in superior performers but varied in inferior performers. 5. It appears best to err on the side of rehearsing for too long than too short. 6. The skill of mental rehearsal should be learned by training specifically for particular situations as if in simulation mode. Implication: Mental imagery has to fully replicate a performance and be of sufficient intensity to cause minor motor responses. This feature has to be learned so that the imagery becomes a consistent skill.